The effectiveness of website-based learning media on the reading comprehension skills of fifth grade students in elementary schools - Sutrisno, Detria Nur Aini; Slamet , St.Y.; Yulisetiani , Septi (Universitas Ahmad Dahlan, 2025)
Learning media has a crucial role in improving students' skills. Recently learning media in the form of Website based learning medias has been very popular with elementary school students. This quasi-experimental study aims to test the effectiveness of Website media in learning reading skills in grade V Elementary School. Randomly class VA was assigned as an experimental class, taking reading lessons using Website media, and class VB, as a control class, participating in reading lessons using ordinary picture media. Data collection techniques use performance tests to assess 6 aspects of reading skills, namely accuracy in voicing writing, pronunciation reasonableness, intonation, fluency, voice clarity, and word understanding. The validity of the test items ranged from 0.65 – to 0.70, with a reliability index of 0.704. The average value of reading skills from the experimental class students' pre-test results was 51.96, and 51.61 in the control class students. From the different test results, the pretest score obtained a t value of 0.887 at sig. 0.380. It can be concluded that there is no difference in reading skills between the two groups before the treatment was carried out. After the learning was carried out, the average post-test scores of the experimental class students were 83.44 and 74.14 control class students. The results of hypothesis testing obtained a value of t 5,205 on sig. 0.000. It can be concluded that there is a very significant difference in reading skills between the experimental class and the control class. The study concluded that the Website based learning media was effective for improving the reading skills of fifth-grade elementary school students.